AB1119 The Cretan Lupus Registry "Leto": Prevalence, Clinical Features and Environmental Factors in a Genetically Homogenous, Mixed Urban and Rural, South European Population. (9th June 2015) - Gergianaki, I.; Fanouriakis, A.; Repa, A.; Pompieri, A.; Kabouraki, E.; Spyrou, G.; Tzanakakis, M.; Kallitsakis, I.; Mamoulaki, M.; Katzakis, P.; Chatzi, L.; Sidiropoulos, P.; et al.
Abstract : Background: Crete is the third largest and southernmost island in the Mediterranean with a relatively stable, genetically homogeneous population of ∼0.6M inhabitants, thus offering the opportunity to study the prevalence, etiopathogenesis and natural history of complex diseases such as systemic lupus erythematosus (SLE). In Crete, 53% of the inhabitants reside in rural, 8% in suburban (10, 000-15, 000 dwellers) and 39% in urban areas (>15, 000 dwellers). Objectives: To establish a registry of SLE patients, designed to estimate the prevalence and incidence of SLE in Crete and describe the disease burden, assessing the impact of place of residency and environmental exposures on disease outcomes. Methods: Case finding was performed from multiple sources, including outpatient clinics, private specialists and administrative-hospitalization databases. SLE cases fulfilling the ACR classification criteria and residing in Crete during 1999–2013 were included. In- and outpatients are prospectively evaluated. Socio-demographic, clinical characteristics (disease activity/severity, damage, comorbidities, quality of life scores) and environmental exposures are electronically registered using structured forms. Results: A total of 733 SLE patients aged ≥15 years who reside permanently on Crete were identified, corresponding to age-adjusted prevalence of 141 per 100, 000 residents. Higher prevalence rates were found in urban versus rural population. This is a population of homogenous socio-demographic (Greek ethnicity 97%, married 81%, educational level <12ys 70%) and genetic (80% of Cretan descent) characteristics. The annual incidence of SLE among adults in Crete is shown in Figure 1 . The average age at the time of diagnosis is 43 (±15) years (range 9-81) with female:male ratio 13:1. Eighty-six (12%) patients have biopsy-proven lupus nephritis and 69 patients (9%) have primary neuropsychiatric lupus. After average follow-up of 8 (±7) years, 47% patients have accrued damage (SLICC/ACR damage index >0), with increased prevalence of damage in rural versus urban residents (49% versus 44%, respectively). Analyses are underway to assess the effects of urbanization, lifestyle habits and environmental exposures on disease outcomes. Conclusions: Longitudinal studies with genetically homogenous, mixed urban and rural population in a setting that combines primary, secondary and tertiary care are instrumental in the description of complex diseases such as SLE, and in determining socio-demographic, environmental and other factors that affect its natural history. SLE prevalence in Crete was comparable to other European centers but with less severe manifestations. References: Somers EC, Marder W, Cagnoli P. et al Arthritis Rheumatol 2014;66(2):369-78. Population-based incidence and prevalence of systemic lupus erythematosus: the Michigan Lupus Epidemiology and Surveillance program. Acknowledgements: This work was supported by grants from the Greek General Secretariat of Research and Technology (Aristeia I 2344). Disclosure of Interest: None declared